Finger-worn assistive device for detection tracking and recognition - Imtiaz, Sharjeel; Khatri, Avais; Motan, Imaad Ud Din; Shaikh, Faraz Ahmed; Khan, Sheroz (Institute of Electrical and Electronics Engineers Inc., 2018)
This paper describes the design and development of the Smart Eye Assistive device. The domain of Finger-Worn assistive devices as user interfaces has only recently begun to be explored and the miniaturization of technology has enabled us to develop a device, which utilizes natural pointing gestures to connect the user with his/her surroundings. In the following paper, the development of the Smart Eye Hardware Software is presented. Utilizing off-self components, and image processing algorithms based on MATLAB image processing toolbox, scenarios where the Smart Eye can be an effective tool for day-to-day interaction, reactions from users as well as its drawbacks are discussed and a conclusion is reached, that such a finger worn device is highly viable for future development.